Loyang Mendale and Loyang Ujung Karang Sites and Their Potential as Sources for Learning History - Angga Prasetiya; Suryo Ediyono (Universitas Syiah Kuala, 2022)
This study aims to describe how the Loyang Mendale and Loyang Ujung Karang sites, based on their relics have the potential as a source of historical learning. The research method used in this research is descriptive qualitative method. Sources of literature in the study came from scientific articles and books related to the excavation results of the Loyang Mendale and Loyang Ujung Karang sites. The results of this study are to describe findings of Hoabinh cultural tools from the Mesolithic period, to Austronesian cultural tools from the Neolithic period at both sites. Based on the results of the archaeological finds, the Loyang Mendale and Ujung Karang sites have the potential to be used as sources for learning history, and can be grouped into KD 3.4 and 4. 4 in the Indonesian History subject class X with the teaching material of prehistoric Life in Indonesia. Learning history by using local pre-historic cultural relics is expected to foster students' interest in loving the history of their area.